Effectiveness of universal programmes for the prevention of suicidal ideation, behaviour and mental ill health in medical students: a systematic review and meta-analysis. Issue 2 (27th March 2019) - Witt, Katrina; Boland, Alexandra; Lamblin, Michelle; McGorry, Patrick D; Veness, Benjamin; Cipriani, Andrea; Hawton, Keith; Harvey, Samuel; Christensen, Helen; Robinson, Jo
Abstract : Question: A growing body of work suggests that medical students may be particularly at risk of mental ill health, suicidal ideation and behaviour, resulting in recent calls to develop interventions to prevent these outcomes. However, few reviews have synthesised the current evidence base regarding the effectiveness of these interventions and provided guidance to improve future intervention efforts. Study selection and analysis: The authors conducted a systematic review to identify studies of any design reporting the effectiveness of any universal intervention to address these outcomes in medical students. Embase, MEDLINE and PsycINFO databases were searched from their respective start dates until 1 December 2017. Findings: Data from 39 studies were included. Most investigated the effectiveness of relatively brief interventions designed to reduce stress; most commonly using mindfulness-based or guided meditation approaches. Only one implemented an intervention specifically designed to address suicidal ideation; none investigated the effectiveness of an intervention specifically designed to address suicidal behaviour. Five investigated the effects of curriculum-level changes. Overall, there was limited evidence of an effect for these programmes at both the postintervention and longest follow-up assessment on depression, anxiety and stress. Conclusions: Relatively brief, individually focused, mindfulness-based interventions may be effective in reducing levels of anxiety, depression and stress in medical students in the short term. Effects on suicidal ideation and behaviour, however, remain to be determined. There has been a significant lack of attention on organisational-level stressors associated with medical education and training.